(untitled) (American Journal of Research in Humanities and Social Sciences, 2025)
This article examines the impact of air pollution in Uzbekistan on the health of students at the Tashkent Medical Institute. Due to the increasing level of air pollution in large cities, especially in Tashkent, the risk of various diseases among young people, including respiratory, cardiovascular and allergic disorders, increases. The article analyzes existing research on this issue, as well as the results of a survey of TMA students regarding their well-being in polluted air. Recommendations for improving the situation at the level of government and educational institutions are included.